(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Níkora A. O. Formation of subject-historical competencies as a result of pupils educational activity. The concept vehicle of the competency building approach is specified in the article, the list of object-historical competences of students and direction of their acquisition is specified in the process of study of history.